Aberrant DNA methylation of DLX4 and SIM1 is a predictive marker for disease progression of uterine cervical low‐grade squamous intraepithelial lesion. Issue 6 (22nd January 2015) - Sakane, Junichi; Taniyama, Kiyomi; Miyamoto, Kazuaki; Saito, Akihisa; Kuraoka, Kazuya; Nishimura, Toshinao; Sentani, Kazuhiro; Oue, Naohide; Yasui, Wataru
Abstract : Background: A few uterine cervical low‐grade squamous intraepithelial lesions (LSILs) are known to progress with high‐risk human papillomavirus (hrHPV). Methods: One hundred and thirteen patients were classified into four groups according to their cervical cytology, hrHPV infection, and follow up. Cytology samples were examined for aberrant DNA methylation of DLX4 and SIM1 genes and protein expressions. CaSki cells were treated with 5‐Aza‐2′‐deoxycytidine (5‐aza‐dC). Results: Group 1 was negative for intraepithelial lesions or malignancies. LSIL in group 2 showed a continuance of LSIL for longer than 365 days and LSIL in group 3 showed an upgrading to high‐grade (H) SIL or higher (HSIL+) within 365 days of LSIL diagnosis. Group 4 was squamous cell carcinoma. All but group 1 were infected with hrHPV. Significant differences existed in the frequency of DNA methylation between groups 2 and 3 (p = 0.044), between groups 3 and 4 (p = 0.020) for DLX4, and between groups 1 and 3 (p = 0.0003), and groups 2 and 3 (p = 0.005) for the SIM1 gene. DLX4 protein expression was significantly reduced in the DLX4 methylation positive tissues (p = 0.008). The 5‐aza‐dC treatment restored DLX4 mRNA expressions of CaSki cells (p < 0.005). The LSIL cases with DNA methylation of the SIM1 gene, or both genes, progressed faster to HSIL+ than did the others (p = 0.033 and p = 0.045, respectively). Conclusion: Aberrant DNA methylation of the DLX4 and SIM1 genes should be a novel progression marker for uterine cervical LSIL with hrHPV infection. Diagn. Cytopathol. 2015;43:462–470. © 2015 Wiley Periodicals, Inc.